Perinatal Complications and Delivery Route in Newborns from Early and late Teenage Mothers, 1995-1997 - Yu-Tang Morales, Jorge (2000)
OBJECTIVES: To know the perinatal complications and delivery route in newborns from early and late teenage mothers. MATERIAL AND METHODS: Analytic, observational and comparative trial between early and late teenagers respect to delivery route and perinatal complications in the Hospital Nacional Daniel A. Carrión, between January 1995 to December 1997. RESULTS: 18,6% of deliveries were in teenagers; 21% were dystocic ones, more frequent in early teenagers (p <0,05). Low birth weight newborns and those with perinatal complications were also frequent in this group (p <0,05). CONCLUSION: Early teenagers had higher risk to present maternal and perinatal complications than late ones.